Essential Oil from Myrcia ovata: Chemical Composition, Antinociceptive and Anti-Inflammatory Properties in Mice - dos Santos, Gabriela Carmelinda Martins; Gomes, Geovany Amorim; Gonçalves, Gabriela Mastrangelo; de Sousa, Leôncio Mesquita; Santiago, Gilvandete Maria Pinheiro; de Carvalho, Mário Geraldo; Marinho, Bruno Guimarães (Planta Medica, 2014)
The leaves of Myrcia ovata, popularly known as “laranjinha do mato”, are frequently used as an infusion in folk medicine. The essential oil obtained from these leaves is rich in citral, a mixture of neral and geranial isomers, known for its analgesic effect. Male Swiss mice (20–22 g) were tested in models of acute pain (acetic acid-induced abdominal writhing, tail flick, and formalin tests) and acute inflammation (paw oedema and air pouch tests) as well as in a model for evaluation of spontaneous motor performance (open-field test). The essential oil from M. ovata was administered orally at doses of 50–300 mg/kg. In addition, water, vehicle, morphine (5.01 mg/kg for evaluation of pain and motor performance), acetyl salicylic acid (200 mg/kg in the formalin test), and dexamethasone (2.25 mg/kg for evaluation of oedema formation, leukocyte extravasation, and quantification of cytokines) were administered. The essential oil showed a significant effect at doses of 200 and 300 mg/kg in the acute pain and acute inflammation tests. The effect of the essential oil was reduced by pretreatment with naloxone. The essential oil did not induce motor impairment. The extract was not toxic after oral administration (LD50 > 3000 mg/kg). These data provide initial evidence that the traditional use of M. ovata can be effective in reducing pain and inflammation.
Keywords: Myrtaceae; Myrcia ovate; acute pain; essential oil; mice